Cold deep subduction recorded by remnants of a Paleoproterozoic carbonated slab - Cheng Xu (Nature Portfolio, 2018)
The onset of modern-style plate tectonics remains under debate. Here, Xu et al. report a cold thermal-gradient recorded in an eclogite xenolith in Paleoproterozoic carbonatite from orogen, and propose that modern-style subduction has operated since at least the Paleoproterozoic.